Vocational training as a framework condition for a successful energy transition using hydrogen as an example - Zinke, Gert [Verfasser] (My University, 2024)
„Which role will hydrogen play in achieving German climate targets through the transition to renewable energy. The German government aims to build 10 GW of green hydrogen capacity by 2030, with a focus on electrification, decarbonisation, and multifunctional hydrogen applications. The importance of training skilled workers for hydrogen-related fields is emphasised, acknowledging the need for a corresponding infrastructure. Two projects funded by the Federal Ministry of Education and Research address the quantitative and qualitative demand for skilled workers in the hydrogen value chain. Sector analyses reveal a projected increase in the labour force by 61,000 persons by 2045, with a net job creation. The impact on skilled workers at all qualification levels is discussed, particularly in intermediate-skilled occupations related to hydrogen.“ (author‘s abstract; BIBB-Doku)
Keywords: G 1.2.4.1.5 Energie- und Wasserversorgung; G 1.2.3.2 Anforderungen & Bedarfe; 370; 330; Energiewirtschaft; Wasserstoffwirtschaft; Klimaschutz; Fachkräftebedarf; Qualifizierung